Intertext and Allusion in the Qur’anic Presentation of Noah’s Story - Abdul-Samad Abdullah (International Institute of Islamic Thought, 2008)
This study explores the Qur’anic presentation of the story of Noah and his people. In particular, it examines the purposes behind the variations and similarities found in the s´rahs that mention it and focuses on three fundamental aspects: linguistic or stylistic variations, religious or moral purposes that determine a particular linguistic or stylistic register and contextualize the story within a particular s´rah, and the extent to which the style serves that s´rah’s objectives. Moreover, while this story has very clear and consistent themes, each s´rah’s concern and context to some extent shapes its rendering therein. Hence, I propose that the repetition of this story is a response to a particular context or conforms to the particular aims and objectives of the s´rah in which it appears. This repetition or intertext and allusion therefore become desirable, if not necessary, for both religious and stylistic requirements.